The Disappearance Behavior, Residue Distribution, and Risk Assessment of Kresoxim-Methyl in Banana (Musa nana Lour.) Based on a Modified QuEChERS Procedure Using HPLC-MS/MS - Wang, Siwei; Sun, Haibin; Liu, Yanping; Wang, Xiaonan; Chang, Hong (Frontiers in Environmental Science, 2022)
A modified-QuEChERS method to determine kresoxim-methyl in banana and soil was developed and validated via high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS). The dissipation behavior, residue distribution, and risk assessment of kresoxim-methyl in banana were further investigated based on this method. The dissipation behavior of kresoxim-methyl in banana and soil was described by using first-order kinetics and its half-life, 4.8–5.7 days and 5.5–6.5 days, respectively. The concentrations of kresoxim-methyl were 0.03–0.08 mg kg−1, 0.06–0.17 mg kg−1, and <0.01 mg kg−1 for a whole banana, peel, and pulp, respectively, on the basis of spraying three times the recommended dosage and pre-harvest interval (PHI, 42 days). The results showed that the risk quotient of kresoxim-methyl in banana to people exhibited an acceptable low dietary risk. This current study could help in guiding the scientific and proper usage of this formulation.